Electrochemical sensing of oxygen gas in ionic liquids on screen printed electrodes - Lee, Junqiao (Curtin University, 2014)
This work aimed to investigate the potentiality of screen-printed electrodes, in room-temperature ionic-liquids (RTILs) electrolytes, for the amperometric sensing of gases. Oxygen was selected as the model gas for these studies. It was found that with proper pre-treatment, these ‘single-use’ electrodes were reusable, their long-term sensing performances were drastically improved, and their robustness was enhanced by polymer-gelification of the RTIL-electrolyte. These studies provide the foundation for future portable sensing application.